KONSEP E-LEARNING DAN APLIKASINYA PADA LEMBAGA PENDIDIKAN ISLAM - Lailatu Rohmah (AN NUR: Jurnal Studi Islam, 2011)
The development of technology and information influences change and progress in education,including the presence of e-learning that is applied in the system of learning in variouseducational institutions. With a variety of advantages and limitations, e-learning has beenapplied in several Islamic Educational Institutions in our country, ranging from Islamicboarding schools, Islamic schools (madrasah) to Islamic universities. The implementationof this e-learning provides new value and color to the world of Islamic education, namelye-learning is more inclusive, flexible, and responsive to the development of civilization.